2015
DOI: 10.1536/ihj.14-250
|View full text |Cite|
|
Sign up to set email alerts
|

Fulminant Type 1 Diabetes Mellitus and Fulminant Viral Myocarditis

Abstract: SummaryA 35-year-old Japanese woman was admitted with coma following flu-like symptoms. She was diagnosed with diabetic ketoacidosis and fulminant type 1 diabetes (FT1D) and received intravenous infusion of insulin and saline. The next day, the ketoacidosis disappeared, and she recovered consciousness. However, extensive ST-segment elevations in the electrocardiogram appeared with a positive troponin test, and the patient developed pulmonary edema on day 3. An echocardiogram showed globally reduced wall motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…Some cases showed the elevation of pancreatic exocrine enzymes with pancreatic swelling before the onset of FT1D [10]. Regarding myocarditis associated with FT1D, it has been reported that 4 cases developed myocarditis several days after symptoms of FT1D [5]. Our patient showed pancreatitis, FT1D and myocarditis consecutively in short period.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Some cases showed the elevation of pancreatic exocrine enzymes with pancreatic swelling before the onset of FT1D [10]. Regarding myocarditis associated with FT1D, it has been reported that 4 cases developed myocarditis several days after symptoms of FT1D [5]. Our patient showed pancreatitis, FT1D and myocarditis consecutively in short period.…”
Section: Discussionsupporting
confidence: 48%
“…However, the etiology of FT1D remains elusive. Several cases with concomitant acute pancreatitis [ 3 , 4 ] or myocarditis [ 5 8 ] during the clinical course of FT1D were previously reported. Herein, we describe a 31-year-old Japanese woman with FT1D who was initially diagnosed with acute pancreatitis and then developed diabetic ketoacidosis and myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient presented with fever and fatigue without any other symptoms before developing FT1D, and the Coxsackie A2 virus infection was confirmed serologically. Table 2 summarizes the reported cases in which virus infection was proven to be involved in the development of FT 1D (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These cases include adults of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…There are two other cases reported in adults. In the first one, parainfluenza 3 viral infection was considered to be the cause of a fulminant myocarditis with pericardial effusion in a 35-year-old woman with diabetic ketoacidosis and type 1 diabetes [3]. The second one described a 62-year-old woman with pneumonia and pericardial effusion as a result of infection with parainfluenza virus type 4 and thrombotic thrombocytopenic purpura [4].…”
Section: Discussionmentioning
confidence: 99%